Global food demand and the contribution of livestock as we enter the new millennium - Delgado, Christopher L.; Courbois, Claude; Rosegrant, Mark W. (International Food Policy Research Institute, 1998)
People in developed countries currently consume about 3 to 4 times as much meat and fish, and 5 to 6 times as much milk products per capita as in developing Asia and Africa. Meat, milk, and fish consumption per capita has barely grown in the developed countries as a whole over the past 20 years. Yet poor people everywhere clearly desire to eat more animal protein products as their incomes rise above poverty level and as they become urbanized. Growth in per capita consumption and production has in fact occurred in regions such as developing Asia, and most particularly China. Per capita consumption of animal proteins and use of cereals as feed in Asia have both grown in the 3 to 5 percent per annum range over the past 20 years. By 2020, according to IFPRI’s IMPACT model projections, the share of developing countries in total world meat consumption will expand from 47 percent currently to 63 percent. IMPACT projections under various technical and economic assumptions suggest that there is enough production supply response in world systems to accomplish these production increases smoothly. Sensitivity analysis of the impact of restrictions on China’s ability to produce more feedgrains illustrates that in a system of linked global markets for cereals and livestock products, such restrictions are not effective at lowering Chinese livestock consumption, which is driven by global trade in manufactures, although they do lower Chinese livestock production. The resulting imbalance raises world feed costs by one-third in 2020 over anticipated levels, encourages increased livestock exports from Latin America, discourages livestock exports from the U.S., and reduces meat and cereals imports and consumption in the poorer countries of Africa and Asia.